Nutritional strategies of physically active subjects with muscle dysmorphia - Contesini, Nadir; Adami, Fernando; Blake, Márcia De-Toledo; Monteiro, Carlos Bm; Abreu, Luiz C.; Valenti, Vitor E. [UNESP]; Almeida, Fernando S.; Luciano, Alexandre P.; Cardoso, Marco A. [UNESP]; Benedet, Jucemar; De Assis Guedes de Vasconcelos, Francisco; Leone, Claudio; et al. (Springer Nature, 2013)
Background: The aim of this study was to identify dietary strategies for physically active individuals with muscle dysmorphia based on a systematic literature review. Method. References were included if the study population consisted of adults over 18 years old who were physically active in fitness centers. We identified reports through an electronic search ofScielo, Lilacs and Medline using the following keywords: muscle dysmorphia, vigorexia, distorted body image, and exercise. We found eight articles in Scielo, 17 in Medline and 12 in Lilacs. Among the total number of 37 articles, only 17 were eligible for inclusion in this review. Results: The results indicated that the feeding strategies used by physically active individuals with muscle dysmorphia did not include planning or the supervision of a nutritionist. Diet included high protein and low fat foods and the ingestion of dietary and ergogenic supplements to reduce weight. Conclusion: Physically active subjects with muscle dysmorphia could benefit from the help of nutritional professionals to evaluate energy estimation, guide the diet and its distribution in macronutrient and consider the principle of nutrition to functional recovery of the digestive process, promote liver detoxification, balance and guide to organic adequate intake of supplemental nutrients and other substances. © 2013 Contesini et al.; licensee BioMed Central Ltd.
Keywords: Diet; Muscle dysmorphia; Nutrition; Physical exercise; fat; protein; bibliographic database; body image; diet supplementation; dietary intake; dietitian; distorted body image; electronic medical record; exercise; feeding behavior; fitness; food intake; fruit; human; low fat diet; Medline; milk; muscle dysmorphia; muscle malformation; muscle mass; nutrition; nutritionist; physical activity; protein diet; review; rice; systematic review; vigorexia; weight reduction